Hubungan riwayat kesehatan gigi ibu dengan stunting pada anak di Puskesmas Lamno, Aceh Jaya - Wirza, Wirza; Sri, Maya Yunita; Febriani, Henny (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Child stunting affects many countries, including Indonesia. Aceh is the province with the highest prevalence of stunting and is in the top five in Indonesia, reaching 31.2%. Aceh Jaya stunting rate in 2023 reached 34% and Lamno Health Center contributed the most, namely 15.97%, dental health data aged 15-44 years more in women (32.60%).Objectives: This study aims to determine the relationship between maternal dental health and stunting in children in Lamno District.Methods: Quantitative research using a crossectional design was conducted in Lamno District in 2023. The sample consisted of 97 children under five years old and their mothers. Dental health history data was obtained from secondary data at the Health Center, while stunting data was obtained through anthropometric measurements (TB/U). Data analysis used Chi-square test at 95% CI.Results: The results showed that the highest number of mothers who did not have a history of oral disease and stunting (36.6%) and did not show an association between the history of dental disease in mothers with the incidence of stunting in children in Lamno District, Aceh Jaya (p = 0.596).Conclusion: Maternal dental health history has no association with the incidence of stunting in children at Lamno Health Center, Aceh Jaya.